EXPERIENCE OF CHRONIC LYMPHOPROLIFERATIVE DISORDER CASES IN A NEWLY ESTABLISHED FLOW CYTOMETRY LABORATORY IN A TERTIARY CARE HOSPITAL: A SERIES OF 8 CASES - RAJANI RAJKUMARI; VIJAY RAJAK; GUNJA DWIVEDI; SWATI AGARWAL (Asian Journal of Pharmaceutical and Clinical Research, 2024)
Chronic lymphoproliferative disorder (CLPD) represents a heterogenous group of conditions affecting lymphocytes – especially white blood cells crucial for combating infections. The utilization of flow cytometry for immunophenotyping has significantly improved the diagnosis and differentiation between various CLPDs. The diagnosis of CLPD is based on the findings of peripheral blood smear, bone marrow aspiration and flow cytometry examinations. Here, we report a series of eight cases, diagnosed as CLPD by flow cytometry out of a total 78 cases received for flow cytometry analysis for a period from March, 2022 to March, 2024 after the establishment of a new flow cytometry laboratory